Antidepressants and Valvular Heart Disease: A Nested Case–Control Study in Taiwan. Issue 14 (April 2016) - Lin, Chia-Hui; Hsiao, Fei-Yuan; Liu, Yen-Bin; Gau, Susan Shur-Fen; Wang, Chi-Chuan; Shen, Li-Jiuan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Empirical evidence regarding the association between antidepressants and valvular heart disease (VHD) is scarce. Using Taiwan's National Health Insurance Research database, this nested case-control study assessed the association between antidepressants and VHD in a Chinese population. Among a cohort of patients who used at least 3 prescription antidepressants, 874 cases with VHD and 3496 matched controls (1:4 ratio) were identified. Conditional logistic regression models were used to examine the timing, duration, dose and type of antidepressants use, and the risk of VHD. Current use of antidepressants was associated with a 1.4-fold increase in the risk of VHD (adjusted odds ratio [aOR] 1.44; 95% confidence interval [CI] 1.17–1.77). Among current users, a dose–response association was observed in terms of the cumulative duration and the cumulative antidepressant dose. Significantly higher risks of VHD were observed among the current users of tricyclic antidepressants (aOR 1.40 [1.05–1.87]). We found that the use of antidepressants was associated with a greater risk of VHD and that the risks varied according to different antidepressants.